2021
DOI: 10.1111/pan.14225
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pediatric MRI sedation/anesthesia at a tertiary medical center over time

Abstract: Background: Each year, hundreds of thousands of children require sedation/anesthesia to facilitate MRI scans. Anesthetic techniques for accomplishing sedation/anesthesia vary widely between institutions and providers, with unclear implications for patient safety. Aims:We sought to establish trends in anesthetic practice for pediatric MRI sedation/ anesthesia across a 7-year period and determine rates of adverse events, considering technique used, age, and ASA physical classification status (ASA-PS).Methods: Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…This study investigated the trends and patterns of sedatives and in- remains the most popular sedative agent because of its rapid onset and emergent properties. 20,21,22 In Japan, propofol is off-label for sedation outside the operating room and is used with caution due to reports regarding its association with some deaths in pediatric patients. 23 Contrastingly, our results revealed that oral triclofos sodium was the most commonly used sedative (51.7%).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the trends and patterns of sedatives and in- remains the most popular sedative agent because of its rapid onset and emergent properties. 20,21,22 In Japan, propofol is off-label for sedation outside the operating room and is used with caution due to reports regarding its association with some deaths in pediatric patients. 23 Contrastingly, our results revealed that oral triclofos sodium was the most commonly used sedative (51.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In their article, the authors describe a shift to a TIVA combination of propofol and dexmedetomidine, eventually representing almost 50% of all anesthetic techniques. 1 While the overall rate of respiratory adverse events (AEs) or physiologic perturbations was low and major AEs were rare, the authors reported that volatile anesthesia compared with a TIVA technique was an independent predictor of AEs consistent with reports of increased AEs with inhalation compared with an iv induction and TIVA being associated with less perioperative airway reflex responsiveness including in an MRI setting. 2,3 Given the low percentage of volatile-only anesthesia reported (≤2.8%/year), the majority of anesthetics appear to have used a natural airway.…”
mentioning
confidence: 83%
“…Data sharing is not applicable to this article as no new data were created or analyzed in this study. Kimmo Murto 1,2 Barry Smith 3,4 Leigh Banfield…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current issue, Vinson and colleagues describe the change in anesthetic MRI regime over a 7-year period by retrospectively reviewing more than 24 000 anesthetics in a major pediatric tertiary hospital and analyzing the incidence of anesthesia-related adverse events (hypotension, bradycardia, and desaturation). 2 During the study period, propofol as sole agent (employed >60% of the time in 2013) was replaced by the combination propofol/dexmedetomidine (employed >45% of the time in 2019). The use of volatiles with propofol remained stable at 15% throughout the years, whereas the combination volatiles/propofol/dexmedetomidine became popular in 2019 (15% of the cases).…”
Section: E D I T O R I a L Anesthesia Service Provision For Mri: Is Shifting The Technique Enough?mentioning
confidence: 99%